1963
DOI: 10.1128/jb.86.3.482-489.1963
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral Colonial Morphology

Abstract: Stalheim , O. H. V. (University of Wisconsin, Madison) and J. B. Wilson . Leptospiral colonial morphology. J. Bacteriol. 86: 482–489. 1963.—A sequence of apparent colonial types was observed with colonies of Leptospira pomona, L. canicola, L. icterohaemorrhagiae , and L. grippotyphosa in agar medium. Although some colonies of these serotypes had a different appearance initially, they eventually developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Although colonial variation in leptospires has been described by Stalheim and Wilson (1963), and although the straight morphological variant has been noted (Simpson and White, 1964), the association of morphology with colonial forms is a new observation. A reasonable explanation would be that the relatively nonmotile straight leptospires tend to proliferate locally, whereas the more motile hooked leptospires travel further in the medium, and produce larger colonies.…”
Section: Discussionmentioning
confidence: 98%
“…Although colonial variation in leptospires has been described by Stalheim and Wilson (1963), and although the straight morphological variant has been noted (Simpson and White, 1964), the association of morphology with colonial forms is a new observation. A reasonable explanation would be that the relatively nonmotile straight leptospires tend to proliferate locally, whereas the more motile hooked leptospires travel further in the medium, and produce larger colonies.…”
Section: Discussionmentioning
confidence: 98%
“…When evidence of growth appeared, 3, 5, or 10 ml was added to 10 ml of synthetic medium containing different concentrations of Tween 80 (0.002, 0.005, 0.007, 0.02, and 0.04%). Observations of the rate and amount of growth were recorded, and the agglutinability of the leptospires was determined as previously described (23,26).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures of derived strains of L. pomona were incubated at 29 C with shaking [110 strokes per min with a 1-inch (2.54-cm) excursion] in Erlenmeyer flasks (1 liter) containing 500 ml of TSM modified by increasing the concentration of Tween 80 to 0.06% (MTSM). The amount of growth was estimated nephelometrically until it was maximal; then the bacterial density was determined by microscopic counts (23).…”
Section: Methodsmentioning
confidence: 99%
“…Larson et al (13) demonstrated that leptospiral colonies were derived from the growth of single cells. It was observed that a sequential change in colonial morphology may occur as the colonies mature (16) and that colonial heterogeneity exists in some serovars of Leptospira (14,16). Studies of three stable and distinct colonial forms of serovar autumnalis provided evidence that no differences existed in their antigenicity or virulence (16).…”
mentioning
confidence: 99%
“…It was observed that a sequential change in colonial morphology may occur as the colonies mature (16) and that colonial heterogeneity exists in some serovars of Leptospira (14,16). Studies of three stable and distinct colonial forms of serovar autumnalis provided evidence that no differences existed in their antigenicity or virulence (16). Faine and Van der Hoeden (7) reported virulence-linked morphological variation in serovar icterohaemorrhagiae.…”
mentioning
confidence: 99%